Electroactive polymer gels as probabilistic reservoir automata for computation - Vincent Strong; William Holderbaum; Yoshikatsu Hayashi (iScience, 2022)
Summary: Electroactive Polymer (EAP) hydrogels are an active matter material used as actuators in soft robotics. Hydrogels exhibit active matter behavior through a form of memory and can be used to embody memory systems such as automata. This study exploited EAP responses, finding that EAP memory functions could be utilized for automaton and reservoir computing frameworks. Under sequential electrical stimulation, the mechanical responses of EAPs were represented in a probabilistic Moore automaton framework and expanded through shaping the reservoir’s energy landscape. The EAP automaton reservoir’s computational ability was compared with digital computation to assess EAPs as computational resources. We found that the computation in the EAP’s reaction to stimuli can be presented through automaton structures, revealing a potential bridge between EAP’s use as an integrated actuator and controller, i.e., our automaton framework could potentially lead to control systems wherein the computation was embedded into the media dynamical responses.